PERSEPSI MAHASISWA UNIVERSITAS RIAU DALAM PELAKSANAAN VAKSINASI MASSA SEBAGAI PENANGGULANGAN COVID-19 DI KAMPUS UNIVERSITAS RIAU - M. Ibnu Aldeyusha; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was motivated by the outbreak of Covid 19 transmission in the community, given the very short time to increase antibodies. Second, the large number of immunization models that have been distributed has made researchers confused in choosing antibody variants. Third, the existence of various measurement periods made students unable to stop thinking about what type of immunization to use and Fourth, said that the group brought by the inoculation coordinator made duplicates of the Corona Virus. The problem in this study is how the perception of Riau University students in carrying out mass immunization as a reaction to COVID-19 in the Riau University environment. The purpose of this study is to find out how the perception of Riau University students in carrying out mass inoculations as a reaction to COVID-19 in the Riau University environment. In addition, it becomes a reference for the most appropriate way to act in public institutions according to the impressions of Riau University students in implementing mass immunization as a reaction to COVID-19 at the University of Riau. This examination was conducted at the Riau University Campus in September 2021 - April 2022. This study used a different quantitative strategy with the population in this study amounting to 31,478 people each year 2018 and the sample in this data collection was taken by means of a purposive examination procedure. with countless 100 people from the student delegation. . So the results obtained in the repetition above are 35.10% + 44.45% = 79.55%. Thus, it tends to be reasonable that the University of Riau Student Perception in the Implementation of Mass Vaccination as a Response to Covid-19 at the Riau University Campus is at the "Very Good" level.Key Words : Perception, Students, Mass Vaccination, University of Riau.